2014
DOI: 10.1051/0004-6361/201322069
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ammonia mapping of the very young protostellar core Chamaeleon-MMS1

Abstract: Aims. The aim of this study is to investigate the structure and kinematics of the nearby candidate first hydrostatic core Cha-MMS1. Methods. Cha-MMS1 was mapped in the NH 3 (1, 1) line and the 1.2 cm continuum using the Australia Telescope Compact Array (ATCA). The angular resolution of the ATCA observations is 7 (∼1000 AU), and the velocity resolution is 50 m s −1 . The core was also mapped with the 64 m Parkes Telescope in the NH 3 (1, 1) and (2, 2) lines. Observations from Herschel Space Observatory and Spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
(129 reference statements)
2
13
0
Order By: Relevance
“…For instance, Tsitali et al (2013) studied the first core candidate Cham-MMS1 and found envelope infall velocities of ∼0.2 km s −1 , an average gradient of 3 km s −1 pc −1 at 1000 AU scales and no signs of a fast, large scale outflow. They concluded that the envelope kinematic properties of this source are consistent with either a first core or a very young Class 0 protostar (see also Väisälä et al 2014).…”
Section: Introductionmentioning
confidence: 84%
“…For instance, Tsitali et al (2013) studied the first core candidate Cham-MMS1 and found envelope infall velocities of ∼0.2 km s −1 , an average gradient of 3 km s −1 pc −1 at 1000 AU scales and no signs of a fast, large scale outflow. They concluded that the envelope kinematic properties of this source are consistent with either a first core or a very young Class 0 protostar (see also Väisälä et al 2014).…”
Section: Introductionmentioning
confidence: 84%
“…Their synthetic observations predicted that the flux of such objects was below the sensitivity of IRAS, even in the nearest star-forming regions, but that they should be detectable by the infrared space observatory (ISO) and Spitzer (at the time known as SIRTF). In reality, the complexity of core structure and fragmentation, coupled with the short lifetime and low flux from first hydrostatic cores made unambigous detection more difficult, though candidates have now been identified and studied in multiple wavelengths, such as B1-bN/B1-bS (Pezzuto et al, 2012), Per-Bolo 58 (Hatchell et al, 2005;Chen et al, 2010;Enoch et al, 2010) Chamaeleon-MMS1 (Belloche et al, 2006;Väisälä et al, 2014), CB17-MMS (Chen et al, 2012) and L1451-mm (Maureira et al, 2017). Tomida et al (2010b) computed radiation hydrodynamic models of low-mass cores with only a small natal envelope.…”
Section: Coresmentioning
confidence: 99%
“…We attempt to fit model SEDs to the observed SEDs of B1-bN and B1-bS (Pezzuto et al 2012;Hirano & Liu 2014), Per-Bolo 58 (Hatchell et al 2005;Enoch et al 2006;Schnee et al 2010;Enoch et al 2010), Chamaeleon-MMS1 (Belloche et al 2006;Tsitali et al 2013;Väisälä et al 2014) and CB17-MMS (Chen et al 2012). Per-Bolo 58 and Chamaeleon-MMS1 are brighter in the infrared than the other FHSC candidates while their SEDs peak at longer wavelengths.…”
Section: Observations Of Fhsc Candidatesmentioning
confidence: 99%
“…Chamaeleon-MMS1. Observational data from Väisälä et al (2014). After SED fits which did not use all six data points were discarded, 17 models fell within a factor of two of the χ 2 value of the best fitting SED.…”
Section: Per-bolo 58mentioning
confidence: 99%
See 1 more Smart Citation